Trends in stratospheric HCl from the ACE satellite mission. (September 2018) - Bernath, Peter; Fernando, Anton M.
Highlights: ACE-FTS on SCISAT measures atmospheric HCl profiles. HCl time series (2004–2017) gives an upper stratospheric trend of −4.8 ± 0.2%/decade. N2 O time series is used to reduce effect of dynamics on the HCl trend. Montreal Protocol continues to be successful in reducing stratospheric chlorine. Abstract: The Montreal Protocol has banned the production of long-lived chlorine-containing gases such as chlorofluorocarbons (CFCs) that deplete stratospheric ozone. These halogenated compounds ultimately form HCl in the upper atmosphere; the effectiveness of the Montreal Protocol can therefore be monitored by measuring stratospheric HCl. The Atmospheric Chemistry Experiment Fourier Transform Spectrometer (ACE-FTS) measures infrared solar occultation spectra of the Earth's atmosphere from which altitude profiles of HCl volume mixing ratios (VMRs) are determined. The upper stratospheric HCl VMR time series has a linear trend of −4.8 ± 0.2%/decade for 2004–2017, highlighting the continuing success of the Montreal Protocol.